Efficacy of Anti-TNFα in Severe and Refractory Neuro-Behcet Disease: An Observational Study. Issue 23 (June 2016) - Desbois, Anne Claire; Addimanda, Olga; Bertrand, Anne; Deroux, Alban; Pérard, Laurent; Depaz, Raphael; Hachulla, Eric; Lambert, Marc; Launay, David; Subran, Benjamin; Ackerman, Felix; Mariette, Xavier; et al.
Abstract : Abstract: To report the safety and efficacy of anti-tumor necrosis factor α (TNFα) therapy in severe and refractory neuro-Behçet disease (NBD) patients. Observational, multicenter study including 17 BD patients (70.6% of male, with a median age of 39.3 [24–60] years), with symptomatic parenchymal NBD, refractory to previous immunosuppressant and treated with anti-TNFα (infliximab 5 mg/kg [n = 13] or adalimumab [n = 4]). Complete remission was defined by the disappearance of all neurological symptoms and by the improvement of radiological abnormalities at 12 months. Overall improvement following anti-TNF was evidenced in 16/17 (94.1%) patients including 6 (35.3%) complete response and 10 (58.8%) partial response. The median time to achieve remission was 3 months (1–6). The median Rankin score was 2 (1–4) at the initiation of anti-TNFα versus 1 (0–4) at the time of remission ( P = 0.01). Corticosteroids have been stopped in 4 (23.5%) patients, and reduced by more than 50% as compared with the dosage at baseline in 10 (58.8%) patients. Side effects occurred in 23.5% of patients and required treatment discontinuation in 17% of cases. TNF blockade represents an effective therapeutic approach for patients with severe and refractory NBD, a difficult to treat population.